CONCEPT OF CHARAKOKTA MEDHYARASAYANAS IN AGE RELATED MILD COGNITIVE IMPAIRMENT (MCI) - Mahajan Madhavi; Parauha Saurabh; Surekha, Sawale (International Journal of Ayurveda and Pharma Research, 2019)
Life expectancy has increased as a result of advancement in medical science. As a result the number of elderly in the population is also greater than ever and there is a need to tackle their problems. Mild Cognitive Impairment (MCI) is one of the most common clinical manifestations affecting the elderly population. This is a transitional stage between the cognitive decline of normal ageing and the more serious decline in dementia. Timely intervention is awfully important in these cases as they are at a high risk of developing dementia. According to Sarangadhara Acharya, Medha (grasping and retention power) deteriorates after the fourth decade of life and this may be considered as a warning signal for further Smriti (memory) and Buddhi (intellect) deterioration, in the successive years. Ayurveda has a major role to play in this arena. The ’Medhya Rasayanas’ are known to be beneficial to improve the intellectual e.g., Mandukparni Swaras, Yashtimadhu Churna with Ksheer, Guduchi Swaras, and Shankhapushpi Kalka. Medhya Rasayana drugs are used for prevention and treatment of mental disorders of all the age groups. These drugs promote the Intellect (Dhi) Retention power (Dhriti), Memory (Smriti). This review discusses about Medhya Rasayanas as a great player for prevention and management of age related cognitive decline.